Error estimates for the semidiscrete finite element approximation of linear nonlocal parabolic equations. (1992) - Jackson, Dennis E.
Abstract : Existence and uniqueness are proved for nonlocal (in time) for solutions of linear parabolic partial differential equations. Instead of an initial condition, there is a relation connecting the initial value to values of the solution at other times. L 2 error estimates are obtained for the semidiscrete approximation of the problem using finite elements in the space variables.